An analysis of Consensus Ad Idem: The Malaysian Contract Law and Shari’ah Perspective - Nik Mahmod, Nik Ahmad Kamal; Abdul Ghani Azmi, Ida Madieha; Engku Ali, Engku Rabiah Adawiah; Wan Ismail, Wan Abdul Fattah; Daud, Mahyuddin; Mohd. Napiah, Mohammad Deen (UPM Press, 2017)
Consensus ad idem (meeting of the mind), is a common law doctrine that requires all parties to the contract to understand and accept the commitments and terms outlined in the agreement. Under the Contracts Act 1950 coercion, undue influence, fraud, misrepresentation and mistake vitiate consent. Equally, under the Shariah, consent or redha constitutes the primary element of a contract. A contract entered into without the consent of contracting parties is either void or can be invalidated; depending on the extent of which such consent is vitiated. This paper discusses factors that vitiate consent under the Contract Act 1950 and compare them with the Shari’ah principles. The objective of this article is to identify whether there is a divergence regarding the understanding of the concept of consensus ad-idem under the Malaysian law and the Shari’ah with the intention of identifying the degree of harmony between the two. Analysis was based on secondary data, namely contract law doctrines, statues and comparing different schools of thoughts in defining Shari’ah principles related to this issue.